Achieving food security: Household perception and adoption of home gardening techniques in Ghana - Irene Serwaa Asante; Magdalene Aidoo; Stephen Prah; Margaret Aba Sam Hagan; Charles Kwame Sackey (Journal of Agriculture and Food Research)
As global food crises and high food prices continue to impact communities, there is a growing focus on strengthening local food systems and improving livelihoods. Home gardening techniques have gained renewed attention as a means of food production and enhancing household food security. However, there is a lack of empirical studies on the perception and adoption of home gardening techniques. This study therefore fills this gap by examining the perception and adoption of home gardening techniques among households in Ghana. A multistage sampling technique was used to select 348 households and data was collected through a structured questionnaire. Using a 5-point Likert scale, we analyzed the households' perception of home gardening techniques, and utilized a multivariate probit regression model to examine the factors influencing multiple adoption of home gardening techniques. The Kendall’s coefficient of concordance was used to test the level of agreement among ranked constraints in adopting home gardening techniques. The generalized Poisson regression was used to examine the number of adoption of home gardening techniques. The results revealed that most households perceived home gardening techniques as a way to improve household food security. Households were found to adopt multiple home gardening techniques, such as use of pots, sacks, and tires. Empirically, factors such as sex, education, occupation, income, technology cost, and social network had a significant influence on multiple adoption of home gardening techniques. Also, age, education, household size, income, technology cost, social network, inadequate space and insect and disease damages significantly influenced the number of adoptions of home gardening techniques. Furthermore, lack of time and inadequate space were the main constraints limiting the adoption of these techniques. We suggest government interventions to spur the adoption of home gardening techniques to improve household food nutrition.